Peran Komunikasi Interpersonal Ustadz Dalam Meningkatkan Nilai-Nilai Akhlakul Karimah DI Pondok Pesantren Darul Ilmi Banjarbaru - Rahidatul Juana; Nina Widyawati; Sanusi Sanusi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Communication interpersonal ustadz is a process interaction in interpersonal done byustadz with students ( santri ) in an effort to give a lesson about akhlakul karimah in a hutpesantren darul ilmi by using verbal communication and nonverbal.This study aims to to see how the role of communication interpersonal ustadz inaccustom children behave aklakul karimah as prayers heads , enforce discipline attitude ,guard cleanliness , keep order , guard honesty and having attitude each other help oneanother in a hut pesantren darul ilmi banjarbaru. Research methodology this is researchdescriptive qualitative.Research carried out in place pondok pesantren darul banjarbaruscienceThe research results show akhlakul karimah in the implementation of the education inpondok pesantren darul ilmi done through three lanes , namely aspects knowledge (cognitive ), aspects the attitude ( affective ) and facets practice in behavior ( psychomotor )dail . So as to achieve the success of the over three aspects, done technique communicationinterpersonal , either in the form of klasikal to a group and to individual. Theimplementation of akhlakul karimah, measured by the six indicators, namely practice andpembiasaan prayer heads, enforcement discipline, keep order, guard honesty, guardcleanliness, and build attitude one another.